FUNGSI LEGISLASI DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) DALAM PEMBENTUKAN PERATURAN DAERAH (PERDA) - Fitrah Malik; Abdul Wahid; Diana Fitriana (Jurnal De Jure Muhammadiyah Cirebon, 2020)
One of the functions of the DPRD is a regional people's representative institution, namely the legislative function. This function is even often referred to as the core of a representative institution, namely as a law-making body within the scope of the region, in other words having the authority to form regional regulations (PERDA). In implementing the policy of making local regulations. The role of DPRD is very large in local government because it is a regional legislative body that functions as one of the institutions that channel people's aspirations in the city of Cirebon. The problem in this study is related to the legislative function of the Regional People's Representative Council (DPRD) in forming Regional Regulations (Perda). This research method is library research (field research) which is descriptive-analytical. The results of this study are the function of the Regional People's Representative Council (DPRD) in line with the People's Representative Council (DPR) in the central government which has an important function in the implementation and administration of government in the regions. Furthermore, the revitalization of the role of the Regional People's Representative Council (DPRD) can be observed in Law Number 32 of 2004 concerning Regional Government, where the Regional People's Representative Council (DPRD) has the authority to make regional regulations (PERDA), budget preparation and supervision, as mandated in Article 41: “Regency/City DPRD has the functions: 1) legislation, 2) budget, and 3) supervision.” Paragraph (2) explains that the three functions as referred to in paragraph (1) are carried out within the framework of people's representation in districts/cities.